Performance Comparison of Conventional PID and Fuzzy Logic Controller in the Field of over headed Water Level Control System - Mondal, Bikas; Billaha, Aref; Roy, Bhaskar; Saha, Rahit (International Journal of Computer Sciences and Engineering, 2025)
Conventional control system adopts PID controller which cannot well adapt to non-linearity, parameter variation, disturbance and change of objective architecture. To strictly limit the overshoot, using fuzzy control we can achieve great control effect. By using fuzzy logic, designers can realize lower development costs, superior features, and better end product performance. The only reasons are faster and cheaper. The Fuzzy control is very much useful for controlling the tank level of the liquid. The purpose of this setup is to design a simulation system of fuzzy logic controller for liquid level control by using Fuzzy Logic Toolbox and MATLAB Simulink software. That’s why in this paper, an attempt is made to compare the control effect due to fuzzy control and conventional PID control and by comparing we will see that fuzzy control is superior to PID control. Result shows that the fuzzy control gives more concentration to different parameters, such as the time of response, the steady state error and overshoot.